Aripiprazole-Induced Oculogyric Crisis: A Pediatric Case Series and A Brief Narrative Review - Pia Bernardo; Alfonso Rubino; Claudia Santoro; Carmela Bravaccio; Marco Pozzi; Simone Pisano (MDPI AG, 2021)
Oculogyric crisis (OGC) represent an unusual type of dystonic movement disorder, usually reported as an adverse event of antipsychotic drugs, with acute or tardive onset, likely due to a functional disruption of dopaminergic neurotransmission. It is seldom reported in children with aripiprazole, an atypical antipsychotic commonly used in youths. In this manuscript, we report on a case series of three pediatric patients and provide a brief narrative review of the literature, in order to increase the awareness of clinicians and to foster future research in this area.